Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Como Uma Canggu Hotel - Ni Made Dwita Wulantari; I Made Sunata (Universitas Triatma Mulya, 2025)
Human assets are the foremost imperative thing in a company since of their part as implementers of the company's operational exercises, so components that influence worker execution ought to be considered, such as workload and work environment. This inquire about points to: (1) decide the impact of workload on representative execution; (2) knowing the impact of the work environment on worker execution; and (3) knowing which free factors have the overwhelming impact on representative execution. The test taken was 55 respondents who were representatives of the COMO Uma Canggu Lodging in North Kuta, Badung, Bali with a examining method utilizing stratified inspecting. Information collection strategies in this inquire about are perception, surveys and documentation. The examination methods utilized are numerous direct relapse examination, T-test, and beta coefficient test. The relapse condition gotten from information handling is Y = 3.464 + 0.652X1 + 0.419X2. The inquire about comes about concluded that: (1) workload had a positive impact on the execution of COMO Uma Canggu Inn representatives in North Kuta Badung Bali (t number 4.132 > t table 2.007); (2) the work environment includes a positive impact on the execution of COMO Uma Canggu Inn workers in North Kuta Badung Bali (t tally 4.961 > t table 2.007); (3) the beta coefficient esteem of the work environment variable is more noteworthy than workload (0.493 > 0.411), so that the work environment contains a more overwhelming impact on the execution of COMO Uma Canggu Inn workers in North Kuta Badung Bali.